Lifestyle Modification in Rheumatoid Arthritis: Dietary and Physical Activity Recommendations Based on Evidence - Chehade, Leila; Jaafar, Zeinab A.; El Masri, Dana; Zmerly, Hassan; Kreidieh, Dima; Tannir, Hana; Itani, Leila; El Ghoch, Marwan (Current Rheumatology Reviews, 2019)
Background: Rheumatoid arthritis is a systemic autoimmune disease, considered the most common inflammatory articular disease among the general population. However, not only the joints are affected; rheumatoid arthritis also has an extra-articular manifestation. As for many other chronic diseases, rheumatoid arthritis may be exacerbated by poorer lifestyle choices. In fact, recent studies emphasize the role of nutrition and physical activity in this disease. Aim: In the current paper, we aim to describe lifestyle modifications based on diet and physical activity and other recommendations that seem to improve the clinical management and the disease outcome of Rheumatoid arthritis. Results: A three-component lifestyle modification programme has been considered based on: (i) A low-fat low-sodium Mediterranean diet rich in fruits, vegetables, whole grains and nuts and poor in sugar-sweetened beverages, red and processed meat and trans fats, and the supplementation with omega-3 fatty acids, non-essential amino acids and probiotics, (ii) An appropriate physical activity programme based on an active daily lifestyle, aerobic exercise and resistance training and (iii) Adequate sleep hygiene and smoking reduction/cessation, that seems to have positive effects in terms of disease progression and related outcomes. Conclusion: Lifestyle modification programme should be considered as the basis of any treatment, (i.e., pharmacological treatment), in patients with rheumatoid arthritis.
Keywords: physical activity